2019
DOI: 10.1002/pra2.175
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of published journals for papers posted on bioRXiv

Abstract: This study investigated papers posted on bioRXiv. In 2013–19, 17,818 papers were published in academic journals, accounting for 40.67% of the total publication. Among them, the Web of Science (WoS) Core Collection recorded journals of 16,525 published papers, accounting for 92.74% of the total. The following conclusions can be drawn. (1) Results indicate scientists' attention to the preprint system. (2) A large number of papers still use traditional publishing as the ultimate goal. (3) Because the posted paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Larivière et al (2014) found that 64% of articles published on arXiv were finally issued in a journal list in Web of Science. In Tsunoda et al (2019) this amounts to about 40%. To summarize, our results are similar.…”
Section: Basic Estimatesmentioning
confidence: 92%
See 1 more Smart Citation
“…Larivière et al (2014) found that 64% of articles published on arXiv were finally issued in a journal list in Web of Science. In Tsunoda et al (2019) this amounts to about 40%. To summarize, our results are similar.…”
Section: Basic Estimatesmentioning
confidence: 92%
“…Abdill and Blekhman (2019) did the same for 37,600 articles from bio R Xiv. Tsunoda et al (2019) also analyzed from bio R Xiv, using a smaller sample of 17,800 articles. Finally, Anderson (2020) shows that over a period of five years 30% of preprints uploaded on bio R Xiv never get published in a journal.…”
Section: Introductionmentioning
confidence: 99%
“…Certain preprint categories are read and shared by both scientists and non-scientists alike [12]. About two-thirds to three-quarters of preprints are eventually published [13,14] and life science articles that have a corresponding preprint version are cited and discussed more often than articles without them [15,16,17]. Preprints take an average of 160 days to be published in the peer reviewed literature [18], and those with multiple versions take longer to publish[18].…”
Section: Introductionmentioning
confidence: 99%
“…The volume of papers posted on bioRχiv has increased rapidly every month (43,812 during November 2013–February 2019). Recently, the server has accepted more than 2,000 papers monthly, 17,818 of which were published, mostly within 6 months (Tsunoda, Sun, Nishizawa, Liu, & Amano, 2019).…”
Section: Resultsmentioning
confidence: 99%